2015
DOI: 10.1098/rsob.150011
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear ionizing radiation-induced changes in eye lens cell proliferation, cyclin D1 expression and lens shape

Abstract: Elevated cataract risk after radiation exposure was established soon after the discovery of X-rays in 1895. Today, increased cataract incidence among medical imaging practitioners and after nuclear incidents has highlighted how little is still understood about the biological responses of the lens to low-dose ionizing radiation (IR). Here, we show for the first time that in mice, lens epithelial cells (LECs) in the peripheral region repair DNA double strand breaks (DSB) after exposure to 20 and 100 mGy more slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 68 publications
2
40
0
1
Order By: Relevance
“…Soon after the discovery of ionising radiation the risk for developing cataracts after exposure to radiation was recognized [180,181]. The lens of the eye is one of the most radiosensitive tissues in the human body.…”
Section: Lens Opacities Among Interventional Cardiologistsmentioning
confidence: 99%
“…Soon after the discovery of ionising radiation the risk for developing cataracts after exposure to radiation was recognized [180,181]. The lens of the eye is one of the most radiosensitive tissues in the human body.…”
Section: Lens Opacities Among Interventional Cardiologistsmentioning
confidence: 99%
“…In this study the mice were all exposed to IR in the morning, the time when proliferation rate would be expected to be highest. Whereas DNA repair in the central, nonproliferative zone was more efficient even than circulating blood lymphocytes from the same animals, lens epithelial cells in the germinative zone had a delayed DNA repair response (30) . Indeed the link between compromised DNA repair and cataract is clear for the lens.…”
Section: Diurnal Changes In the Eye Lens: Cell Proliferation Melatonmentioning
confidence: 99%
“…Previous studies determined that the lens epithelium, and specifically the region where epithelial cell proliferation is concentrated, i.e. the germinative zone where IR effects are seen (12,30) and by preventing cell proliferation, IR-induced cataract is also prevented (31,32) . Given that the lens epithelium also is subject to circadian rhythm for cell proliferation (11) , why is the germinative zone of the lens especially sensitive to IR?…”
Section: Diurnal Changes In the Eye Lens: Cell Proliferation Melatonmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, in several studies it have been shown that this nonlinearity may be due to the DNA repairing induction only after mammalian cell exposure to a dose exceeding 100 mSv [15][16][17]. A DNA doublestrand breaks (DSBs) is reported which occurs within 30 days after the animals were inoculated once with 137 CsCl intraperitoneally, or with a conditionally high (1.55±0.1 MBq) and low (200±0.3 kBq) doses of 85/90 SrCl 2 intravenously [18].…”
mentioning
confidence: 99%